Quantitative framework for prospective motion correction evaluation. Issue 2 (11th March 2015) - Pannetier, Nicolas A.; Stavrinos, Theano; Ng, Peter; Herbst, Michael; Zaitsev, Maxim; Young, Karl; Matson, Gerald; Schuff, Norbert
Abstract : Purpose: Establishing a framework to evaluate performances of prospective motion correction (PMC) MRI considering motion variability between MRI scans. Methods: A framework was developed to obtain quantitative comparisons between different motion correction setups, considering that varying intrinsic motion patterns between acquisitions can induce bias. Intrinsic motion was considered by replaying in a phantom experiment the recorded motion trajectories from subjects. T1‐weighted MRI on five volunteers and two different marker fixations (mouth guard and nose bridge fixations) were used to test the framework. Two metrics were investigated to quantify the improvement of the image quality with PMC. Results: Motion patterns vary between subjects as well as between repeated scans within a subject. This variability can be approximated by replaying the motion in a distinct phantom experiment and used as a covariate in models comparing motion corrections. We show that considering the intrinsic motion alters the statistical significance in comparing marker fixations. As an example, two marker fixations, a mouth guard and a nose bridge, were evaluated in terms of their effectiveness for PMC. A mouth guard achieved better PMC performance. Conclusion: Intrinsic motion patterns can bias comparisons between PMC configurations and must be considered for robust evaluations. A framework for evaluating intrinsic motion patterns in PMC is presented. Magn Reson Med 75:810–816, 2016. © 2015 Wiley Periodicals, Inc.